University rankings in the European Union: a multidimensional approach to a complex reality - Orduña-Malea, Enrique (Anuario ThinkEPI, 2010)
The increasing complexity of the university, augmented by its commoditization, means that the information about its knowledge management is also more complex, whether we consider obtaining, contextualizing or redirecting it to various users. University rankings, despite the criticism they receive, appear as contextualized information tools for each type of user. The main goals of the creation and implementation of the multidimensional global ranking design and testing project, funded by the European Commission on Education, are described.
Keywords: High education market; WTO-GATS; Universities´ ranking; European Union.